What is the best intervention to prevent adolescent pregnancies?. Issue 7 (July 2016) - Gamble, Lena; Dixon, Karen; Smith, Lacy; Waits, John; Way, Nathan; Richardson, Stephen
Abstract : Evidence‐Based Answer : The combination of sexual education and contraception promotion reduces the rate of unintended pregnancy in 10 to 19 year olds by up to 80% (SOR: A, systematic review of RCTs). Contraceptive education with free access to long‐acting reversible contraceptives (LARCs) and other contraceptives also decreases the rate of teen pregnancy (SOR: B, consistent findings from 2 prospective cohort studies).